The role of ergonomics: enhancing educational quality through an optimal learning environment / Santibuana Abd Rahman ... [et al.]. - Abd Rahman, Santibuana; Rosley, Nurhaida; Razali, Azira Iqlima; Sejari, Nurhanisah; Ramly, Mohd. Murtadha; Rafek, Maisarah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The quality of education depends not only on the content and teaching methods but also on ergonomic learning environments. Ergonomics in education refers to adapting the learning environment to meet the physical and psychological needs of both students and educators. For instance, the design of workplaces or learning spaces, the use of appropriate furniture, and adequate lighting to ensure the comfort of both students and educators. Studies have shown that factors such as the design of tables and chairs, the positioning of computer screens and lighting levels can influence concentration and comfort during the learning process (Smith, 2013). However, there has been less focus on macro-ergonomics issues in schools such as discomfort learning environments, mismatch between student body sizes and their tables and chairs, the weight of schoolbags and the prevalence of musculoskeletal disorders amongst school students (Legg & Jacobs, 2008). Therefore, it is essential for educational institutions to consider ergonomic concepts in their efforts to enhance educational quality.